But What About The Big Bad Wolf? Refashionig Red And The Wolf In The 21st Century - Şerban Andreea (Romanian Journal of English Studies, 2015)
This paper aims to revisit three adaptations of Red Riding Hood fairy tales and explore some of the wolf’s reincarnations in order to see how realities change in time. It has generally been observed in the literature that in pop culture Red has undergone quite dramatic changes from the little ingénue to the mature seductress. But what has happened to the bad wolf? How is he imagined by the 21st century pop culture? How do his agency and power change? What (new) message does he convey? To answer these questions, I shall look at three fairly recent advertisements that adapt the classic Little Red story for the screen: “Red Bull” energizer (February 2010), “Chanel no. 5” (featuring actress Estella Warren, late 1990s, 2007) and “B.U. Heartbeat” (featuring Tyson Kuteyi, 2008) perfumes. I will explore not only how such commercials reframe the dominant Western cultural pattern, but if they also undo the lessons both men and women have so far been forced to learn.